Synthesis of hapten, production of monoclonal antibody, and development of immunoassay for ribavirin detection in chicken. Issue 7 (19th June 2021) - Zhu, Jianyu; Li, Qiang; Yu, Xuezhi; Zhang, Xiya; Li, Hongfang; Wen, Kai; Ke, Yuebin; Zhang, Suxia; Wang, Zhanhui
Abstract : Abstract: Ribavirin (RBV) is an effective antiviral drug, whose use is prohibited in animal husbandry worldwide. In this work, a novel immunizing hapten of RBV, named Hapten 4, was designed by comparing the conformational and electronic properties of RBV and haptens based on computational chemistry. Hapten 4 was synthesized and conjugated with carrier proteins to produce monoclonal antibody (mAb). The obtained mAb 4C3 for RBV exhibited an IC50 value of 6.24 ng/ml in an indirect competitive enzyme‐linked immunosorbent assay (icELISA) and displayed no cross‐reaction with five other antiviral drugs, including amantadine. The applicability of the developed icELISA was verified in chicken, with a calculated limit of detection of 4.23 µg/kg. The recoveries in spiked chicken were 79.2%–107.3% with a coefficient of variation less than 15.9%. The results indicated that the produced antibody from the new hapten was reliable and would be useful for RBV screening in chicken. Practical Application: RBV is a broad‐spectrum antiviral drug, which is commonly used illegally in poultry farms. A high‐affinity mAb 4C3 against RBV was produced and used to develop icELISA with acceptable sensitivity and accuracy. The constructed icELISA has excellent performance for detecting RBV residues in chicken.